Strategi Content Creator Bali United Store dalam Mengembangkan Customer Engagement di Tiktok - Larasati Maharani; Hudi Santoso (Universitas Prof. Dr. Moestopo (Beragama), 2026)
Bali United Store, as the official store of the Bali United football club, utilizes its TikTok account as a means of disseminating information and promoting products to fans. This platform is used to strengthen relationships with audiences and build ongoing engagement. This study aims to explain how Bali United Store's TikTok content creators design and manage content in an effort to increase customer engagement during the period from August to December 2025. The research uses a descriptive qualitative approach through observation, interviews, and documentation of content activities on the Bali United Store TikTok account. The analysis refers to The Circular Model of SOME (Share, Optimize, Manage, Engage) as a framework for identifying the application of each stage of the digital communication strategy. The results show that the four stages of the SOME model are consistently applied in content management practices. The share stage is realized through the presentation of club identity-based content and product promotions. The optimize and manage stages are reflected in the selection of appropriate formats and active management of interactions. The engage stage is carried out through efforts to encourage audience participation and responses. This implementation has resulted in increased engagement, expanded content reach, and strengthened brand loyalty for Bali United Store in the digital realm.